Discrete Communication Systems - Berber, Stevan (Oxford Graduate Texts, 2021)
This is the first textbook which presents the theory of pure discrete communication systems and its relation to the existing theory of digital communication. It is written for undergraduate and graduate students, and for practicing engineers.